Distributed Human Interaction Proof for Public Blockchain Platform - Kumar, Mahesh; M, Sindhu; Sethumadhavan, M; K V, Lakshmy (International Journal of Engineering and Technology, 2018)
We introduce the concept Distributed Human Interaction Proof also known as DHIP. DHIP is an adaptation ofCAPTCHAtechnology to the public Blockchain paradigm. CAPTCHAs are helpful to distinguish between humans and bots. All the centralized web applications use CAPTCHA technology to prevent bot attacks. DAPPs like Reputation systems, voting systems are prone to bot based ballot stuffing. Centralized CAPTCHA solutions cannot be applicable to DAPPs. In this paper, we have proposed ways to incorporate the CAPTCHA technology to the public Blockchain paradigm. Our DHIP utility offers CAPTCHA benefits to DAPPs in trustless and distributed way. Formulations of the classes and workflows are discussed. We separated out CAPTCHA provisioning from its validation. CAPTCHA provisioning is handled off the chain but its validation is openly done in a trust less way by our DHIP utility. We have developed the transaction flow for CAPTCHA provisioning and its validation. We have demonstrated our utility with the help of Ethereum platform.Â